2015
DOI: 10.1088/1674-1056/24/5/054210
|View full text |Cite
|
Sign up to set email alerts
|

Generation of isolated attosecond pulses in bowtie-shaped nanostructure with three-color spatially inhomogeneous fields

Abstract: We theoretically investigate high-order harmonic generation in a two-color multi-cycle inhomogeneous field combined with a 27th harmonic pulse. By considering a bowtie-shaped gold nanostructure, the spatiotemporal profiles of enhanced plasmonic fields are obtained by solving the Maxwell equation using finite-domain time-difference method. Based on quantum-mechanical and classical models, the effect of 27th harmonic pulse, temporal profile of enhanced plasmonic field and inhomogeneity on supercontinuum generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The inhomogeneous field E ic (z, t) is a polynomial-type case [24,25,27,31], which is definitely more accurate than the inhomogeneous cases with E ia (z, t) and E ib (z, t), the linear functional forms. In the following discussion, we will compare HHG from 3D H atom in three kinds of inhomogeneous fields together.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhomogeneous field E ic (z, t) is a polynomial-type case [24,25,27,31], which is definitely more accurate than the inhomogeneous cases with E ia (z, t) and E ib (z, t), the linear functional forms. In the following discussion, we will compare HHG from 3D H atom in three kinds of inhomogeneous fields together.…”
Section: Resultsmentioning
confidence: 99%
“…After that, some alternative approaches to realize plasmonic field enhancement were explored by employing different kinds of metallic nanostructures [16,17]. Subsequently, there is a lot of theoretical work [18][19][20][21][22][23][24][25][26] on the characteristic of HHG and attosecond pulse generation of atoms in inhomogeneous field, such as the coherent extreme ultraviolet photons generation beyond the carbon K edge [27], the extension of plateau [28,29], quantum path control [30], wavelength and carrier-envelope phase dependence [31], above-threshold ionization process [32,33], and so on. Most of theoretical study is based on linear-form inhomogeneous electric field, and the comparation between linear-form and polynomial-form fields still needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al 31 obtained a sub-10 as pulse through the combination of the two-color inhomogeneous¯eld. Xue et al 32 theoretically investigated the HHG from the three-color inhomogeneous¯eld and obtained a 35 as pulse. Xiang et al 33 theoretically investigated the HHG from the few-cycle inhomogeneous¯eld and obtained a sub-30 as pulse without any phase compensation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the generations of the HHG and the attosecond pulse driven by the inhomogeneous¯eld in space have been investigated, [21][22][23][24][25][26][27][28][29][30][31][32][33][34] little investigation has been reported on the HHG and attosecond pulse generation driven by the inhomogeneous eld in both space and frequency. Based on the STM, we know that the harmonic cuto® is relevant to both the temporal pro¯le of the laser intensity and the frequency.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the emissions of the signals were the neutral or the ionized gas atoms instead of the HHG. Further, HHG from the nonhomogeneous field received much more attention . For instance, Lewenstein's group presented the quantum and the classical methods to explain the generations and the extensions of the harmonics in the presence of the nonhomogeneous field.…”
Section: Introductionmentioning
confidence: 99%